SOCIAL CAPITAL AND MULTI-STAKEHOLDERS COOPERATION AS A FOUNDATION OF CORPORATE SOCIAL RESPONSIBILITY - Kafa Abdallah Kafaa (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2019)
The discussion of related Corporate Social Responsibility (CSR) in the area of scholarship in Indonesia has been done in any progress. Refers to several studies that have been conducted, the results showed there are still many companies that run CSR programs does more than just as a powerful tool for development and improvement of the company image within the community. By taking the case on Program Pendampingan Posyandu Pelawi Menuju Posyandu Mandiri, leading to this study would be a different and more direct discussion on the explanation of the foundation that supports the sustainability of the program. This study uses qualitative methods with referring to a case study approach. Data obtained in this study is based on two stages, namely: in-depth interviews and field observations. The result shows that social capital and multi-stakeholders cooperation have been put to good use as a foundation of the sustainability program including its activities. However, the program is not free from criticism. Social capital used in the program tend to be exaggerated. When the use of excessive social capital persists, it will make Posyandu Pelawi dependency. Even though, as a preliminary, social support from various parties is very necessary for the Program. The goal efforts of achievement Program from stakeholders are still spontaneity and not specifically.